Modeling for Analyzing Effects of Groundwater Pumping in Can Tho city, Vietnam - N.D.G. Nam; A. Goto; K. Osawa; N.V.C. Ngan (International Association of Lowland Technology, 2019)
In this study, the steady-state groundwater model in the study area, Can Tho city, a capital of Mekong Delta, was developed. To construct the numerical groundwater model for the Can Tho city, the concept and model boundary were set by hydrological data (model layers), digital elevation map (drainage and surface) and Mekong Delta region groundwater model results (groundwater head boundary). Investigation and compilation of data for the model input such as aquifer properties, hydraulic parameters and meteorological data were conducted and initially assigned to the model for a grid cell. The calibrated model successfully simulated groundwater heads comparing with observation heads at 14 monitoring wells. Simulation of spatial groundwater heads distribution of the aquifer includes groundwater pumping stations for domestic and industry was conducted as expected from the conceptual model. Its results clarified groundwater drawdown areas in the city. Impact zones of groundwater pumping are also addressed and known as vulnerable zones to land subsidence. Finally, to understand the effects of projected increased demands on groundwater for water supply, the model was used to predict the groundwater decline based on the trend of increased pumping until 2035. The formation process of cones of depression under current and increased pumping operation was also modeled in 3D to evaluate the impacts of dense distribution of pumping wells on groundwater resources in the Can Tho city.